Subclinical hearing loss and educational performance in children: a national study - Sharma, Rahul K.; Chern, Alexander; Golub, Justin S.; Lalwani, Anil K. (Frontiers in Audiology and Otology, 2023)
Objective Hearing loss can cause speech and language delays, communication barriers, and learning problems. Such factors are associated with reduced academic achievement, social isolation, decreased quality of life, and poorer health outcomes. We use a national cohort of children to examine how subclinical hearing loss is associated with academic/educational performance. The goal of this study is to determine if different levels of subclinical hearing loss (pure tone average ≤ 25 dB HL) are associated with educational testing outcomes in children. Design Analysis of children 6–16 years old who participated in the National Health and Nutrition Examination Survey (NHANES-III, 1988–1994) was performed. Air-conduction thresholds were measured at 0.5, 1, 2, 4, 6, and 8 kHz. A four-frequency pure-tone average (PTA) was calculated from 0.5, 1, 2, and 4 kHz. Hearing thresholds were divided into categories ( ≤ 0, 1–10, and 11–25 dB) for analysis. The outcomes of interest were the Wide Range Achievement Test (WRAT-R) and Wechsler Intelligence Scale for Children (WISC-R). Analysis was conducted using ANOVA and logistic regression. Results We analyzed 3,965 participants. In univariable analysis, the average scores in scaled math, reading, digit span (short-term memory), and block design (visual-motor skills) were significantly lower with worsening hearing categories (p < 0.01). In multivariable regression PTAs of 1–10 dB HL (OR 1.72, 95% CI 1.29–2.29, p < 0.01) and 11-25 dB HL (OR: 2.99, 95% CI 1.3–6.65, p < 0.01), compared to PTA of ≤0 dB HL, were associated with poor reading test performance (<25th percentile). Conclusion Subclinical hearing loss is associated with worse performance on educational attainment (as measured by reading test performance) in children between the ages of 6–16.